La Raffinerie du Plan K : Die 3. + 4. Dimension. - Goethe-Institut, Brüssel; Künstlerhaus Bethanien, Berlin; Plan K, Brussel (Berlin : Künstlerhaus Bethanien, 1984)
Butzmann, Frieder ; Die Tödliche Doris ; Eller, Ulrich ; Gilow, Fritz ; Hanfeld, Folke ; Johansson, Sven Ake ; Julius ; Kapielski, Thomas ; Kummer, Raimund ; Pitz, Hermann ; Radermacher, Norbert ; Raeck, Karina ; Rahmann, Fritz ; Rheinsberg, Raffael ; Santarossa, Hella ; Schulz, Thomas ; Stück, Norbert
La Raffinerie du Plan K : Die 3. + 4. Dimension, Goethe-Institut, Brüssel / Künstlerhaus Bethanien, Berlin / Plan K, Brüssel, November 1984
boek